Adaptive Strategies for Securing Halal Food Among Indonesian Migrant Families in Japan: A Review of Halal Food Literacy - Tarma Tarma; Rahma Shabrina Oktarianti; Prastiti Laras Nugraheni (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the influence of halal food literacy on adaptation strategies for meeting halal food needs among Indonesian migrant families in Japan. A quantitative associative approach was used, with 96 respondents selected via simple random sampling in the Toyota area of Japan. Data were collected through an online questionnaire and analyzed using Spearman’s correlation and non-parametric cubic regression. The results indicate that halal food literacy falls into the moderate category, characterized by a strong reliance on halal labels, while halal awareness remains low. Adaptation strategies also fall into the moderate category, with innovation emerging as the primary form of consumption adjustment. A positive and significant relationship exists between literacy and adaptation strategies, with a high correlation strength. However, this relationship is non-linear, meaning that increased literacy does not always consistently result in increased adaptation. This condition indicates that structural and social factors also influence the adaptation patterns of migrant families in meeting their halal food needs in Japan.